"Proud to be a Special": a qualitative study exploring the experiences of Special Constables in the UK. Issue 3 (14th October 2019) - Plimley, Sarah L.; Krahenbuhl, Sarah
Abstract : Purpose: The purpose of this paper is to understand what motivates members of the public to volunteer within the Special Constabulary and seek to understand their experiences when engaging in this role. There is little qualitative research examining the experiences of volunteers and yet such literature is pivotal in supporting positive future engagement of a valuable resource. Design/methodology/approach: Six currently serving Special Constables (SC) were interviewed about their role. The semi-structured interviews were transcribed and analysed qualitatively through thematic analysis. Findings: Thematic analysis identified four main themes: "Proud to be a Special": active demonstration of pro-social behaviour; "Lines of Division": recognition of distinction between SC and Regular Police Officers; "Levels of Training": adverse consequences of inadequate training; and "Mind the Gap": impact of financial austerity. The SC recognised their role as a utilitarian resource with both positive and negative impacts on all Police Officers. Originality/value: The findings highlighted the need for a careful balance between having enough SC to maintain appropriate policing and yet ensuring opportunity for sufficient experience to develop and implement their skills, successful demonstration of which would support more positive working relationships with Regular Police Officers.